Effects of four natural antioxidant phenyl terpenes on emulsifying and rheological properties of egg yolk. (15th September 2017) - Gouda, Mostafa; Zhang, Shisi; Liu, Yuanyuan; Sheng, Long; Ma, Meihu
Abstract: The objective of this study was to evaluate the effects of the natural safety high antioxidant compounds on egg yolk physical properties. Three different concentrations have been evaluated from: trans-cinnamaldehyde, thymol, menthol or vanillin on egg yolk by measuring the antioxidant activity, emulsification properties, average diameter droplet ( d 3, 2 ), low field nuclear magnetic resonance, viscosity, stress and viscoelastic properties. Results showed that 0.1 g/100 g from vanillin and thymol were the most significant ( P <0.05) antioxidant agents against yolk lipid oxidation with 70.21 ± 0.14 and 51.37 ± 0.09 AI%. Also, thymol 0.1 g/100 g increased the emulsion activity (EA) (0.63 ± 0.01 Abs) significantly ( P <0.05) with increasing the viscosity to 18.09 ± 0.08 Pa s and decreasing d 3, 2 to 2.48 ± 0.01 μm. Moreover, trans-cinnamaldehyde 0.1 g/100 g d 3, 2 decreased significantly ( P <0.05) to 1.61 ± 0.12 μm with increasing ( P <0.05) oil peak surface area to 12.72 ± 0.08 k. au and increasing ( P <0.05) viscosity, stress and viscoelastic properties. Vanillin and thymol showed the most effects on storage modulus (G′), in which it became larger than loss modulus (G″) compared to the control group, which revealed that they can be used for increasing gel-like structure for the egg yolk without using any additional materials. Highlights: Trans-cinnamaldehyde, thymol, menthol and vanillin prevents yolk lipid oxidation. Trans-cinnamaldehyde and thymol improves emulsification and rheological properties. Egg yolk Emulsion activity and rheological properties correlate with droplet size and oil distribution. Vanillin and thymol have high significant effect onto viscoelastic property. Thymol and trans-cinnamaldehyde (0.1%) significantly decrease yolk droplets diameter.